Pemanfaatan Teknologi dalam Pendidikan : Meningkatkan Interaktivitas Pembelajaran - A. Tegar Babur Firdaus; Moh. Ainur Rizal; Thoifur Rahman (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This research examines the use of technology in increasing learning interactivity in Indonesia. The aim of the research is to analyze various forms of educational technology used, identify their impact on learning interactivity, and explore the challenges and opportunities in their implementation. The method used is a systematic literature review by analyzing published scientific articles. The research results show that the use of technology such as learning management systems, augmented reality, and artificial intelligence significantly increases learning interactivity. However, there are challenges such as limited infrastructure and digital competence of educators. In conclusion, the use of technology has great potential in increasing learning interactivity, but requires a comprehensive and sustainable implementation strategy.